2020
DOI: 10.1038/s41529-020-0114-1
|View full text |Cite
|
Sign up to set email alerts
|

Near-field corrosion interactions between glass and corrosion resistant alloys

Abstract: This study explores the corrosion interactions between model nuclear waste glass materials and corrosion resistant alloys, under accelerated conditions that simulate the near field of a nuclear waste repository. The interactions between the corrosion of stainless steel (SS) 316, alloy G30, or alloy 625, and international simple glass or soda-lime silica glass are systematically studied. The dissimilar materials were exposed in close proximity to each other in different electrolytes at 90°C. After exposure, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 66 publications
2
23
1
Order By: Relevance
“…Iron (Fe) concentrations in the ISG systems were lower than the detection limit in the present experiment, which might be owing to its rapid integration into the Si network during the first corrosion phase [16]. Magnesium solubility was observed in various systems.…”
Section: Leaching Solution Analysiscontrasting
confidence: 57%
See 1 more Smart Citation
“…Iron (Fe) concentrations in the ISG systems were lower than the detection limit in the present experiment, which might be owing to its rapid integration into the Si network during the first corrosion phase [16]. Magnesium solubility was observed in various systems.…”
Section: Leaching Solution Analysiscontrasting
confidence: 57%
“…That balance leads to silicate saturation in a solution in which the ultimate silicic acid saturation (H 4 SiO 4 ) occurs. Finally, if the interventions by iron minerals i.e., Ankerite or other geological factors are not carried out [15][16][17][18][19][20][21], the corrosion rate of HLW glass should reach a steady state.…”
Section: Introductionmentioning
confidence: 99%
“…Since the nature of the filling materials is not clearly defined at this point, this study only considers the interface between the canister and ceramics. We have recently reported the potential corrosion interactions between SS and other waste forms in a corrosive environment 9,10 . Synergistic interactions were found between the SS crevice corrosion and the corrosion of Cr-bearing hollandite ceramic waste forms.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive studies have shown that these Si-bearing minerals can enhance glass corrosion by disrupting the steadystate corrosion of glass and triggering the Stage III glass corrosion regime 58 . While the corrosion of glass was clearly enhanced by SS in both DI water and NaCl solution, the effect of glass on the corrosion of SS depended on the solution chemistry 57 . In NaCl solution, the glass corrosion products, primarily silicates, inhibited the corrosion of SS, owing to the suppression of the SS passive film breakdown.…”
Section: Anoxic Environmentmentioning
confidence: 95%
“…In recent studies, a mechanism of nearfield interaction based on metal crevice corrosion was disclosed by Guo et al, as schematically illustrated in Fig. 9 30,45,57 . The authors corroded international simple glass (ISG) or soda lime silica glass (SLSG) in close proximity to SS316, Alloy 625, or Alloy G30 in 0.6 M NaCl solution or DI water at 90°C for 14 or 30 days.…”
Section: Anoxic Environmentmentioning
confidence: 99%